Determinan Resiko Pembiayaan Yang Di Pengaruhi Oleh CAR, Dan Bank Size Survey Pada Perbankan Nasional Syariah - Krisnandi, Herry; Asyari; Yartono, Nungki; Pallawagau, Andi (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
Risk management in Islamic banks is an ongoing process of how banks manage the risks they face. Minimizing the potential for occurrence and the impact on various unwanted risks. The main activities of sharia banking are collectors and channeling funds in the form of murabahah financing to customers, from financing distribution activities that can lead to financing risk, that is problematic customers The research objective is to know the effect of CAR, and Bank size on financing risks simultaneously in the period 2019 - 2023 with a sample of 7 sharia banking company. The test method uses multiple linear regression tests, where the results of this study show that CAR has a significant effect on credit risk (NPL). Bank Size are two variables that have no significant effect on Credit Risk (NPL) for banking companies listed on IDX Islamic, Sharia Stocks.